Regional Migration in West Africa: Trends and Challenges Along NigeriaCameroon Borders - Sambo, Abubakar Mohammed; Mshelia, Abubakar Garba; Othman , Muhammad Fuad; Omar, Rusdi (Kashere Journal of Politics and International Relations, 2023)
The recent development and of course advancement in transportation and communication Ttechnology has brought about an increase in activities along the border-lines in order to augment the economic wellbeing of the people along our international borders; it brings about the upsurge in both the immigration and migration issues along these lines. The nature and character of those drifters on border is for different reasons. People with good, suspicious and questionable characters move in many directions along the Nigeria - Cameroon borders either under the guise of visits to relatives, and or trading activities. Increasing bilateral relations between these two countries, even though not under the same economic bloc within the West African subcontinent, Nigeria and Cameroon need to develop formal social and economic relations despite the language and ’ideological’ barrier or differences, so as to formalise their relationship and address the security issues that mostly occur as a result of colossal immigration along the two borders after having a long pre-colonial historical relationship but with two different colonial and post-colonial political antecedents. This paper attempts to suggest ways of reducing the many illegalities, like smuggling of small firearms and ammunition along the borders of these countries. One major recommendation of this paper is for Nigeria and Cameroon to develop a unique form of bilateral relations so as to capture and address the local business and economic interactions along the communities found along the borders of these two countries.